2023
DOI: 10.3389/fpls.2022.1094194
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids promote Rhizophagus irregularis spore germination and tomato root colonization: A target for sustainable agriculture

Abstract: The use of arbuscular mycorrhizal (AM) fungi has great potential, being used as biostimulants, biofertilizers and bioprotection agents in agricultural and natural ecosystems. However, the application of AM fungal inoculants is still challenging due to the variability of results when applied in production systems. This variability is partly due to differences in symbiosis establishment. Reducing such variability and promoting symbiosis establishment is essential to improve the efficiency of the inoculants. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…In this study, repeated treatments with the C4H inhibitor PIP over a period of a month reduced root colonization by R. irregularis by 50%, although it did not fully abolish symbiosis. Hence, phenylpropanoids and flavonoid derivatives are relevant for symbiosis in citrus, as previously shown in other crops 85,87 . Furthermore, we confirmed that C4H activity is essential for MIR in citrus, because a single treatment with PIP 1 day before infestation abolished MIR.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, repeated treatments with the C4H inhibitor PIP over a period of a month reduced root colonization by R. irregularis by 50%, although it did not fully abolish symbiosis. Hence, phenylpropanoids and flavonoid derivatives are relevant for symbiosis in citrus, as previously shown in other crops 85,87 . Furthermore, we confirmed that C4H activity is essential for MIR in citrus, because a single treatment with PIP 1 day before infestation abolished MIR.…”
Section: Discussionsupporting
confidence: 88%
“…These compounds can serve as natural agents to strengthen plant resistance, reduce the need for chemicals and improve crop quality. In addition, studies have shown that flavonoids can play a fundamental role in promoting plant growth, stimulating nutrient absorption and optimizing metabolic processes ( Lidoy et al (2023) ). Flavonoids show intriguing potential for the development of more sustainable phytosanitary products, as certain varieties have demonstrated pesticidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the signaling role of myristate has also been found in several soil-borne bacteria (Fernández-Piñar et al ., 2012; Liu et al ., 2024), implying its universal role in regulating the soil microbiome. AMF signal molecules such as strigolactones and flavonoids increase AMF colonization by promoting spore germination, and hyphal growth and branching (Mori et al ., 2016; Lidoy et al ., 2023; Yu et al ., 2022); and palmitoleic acid even stimulates asymbiotic AMF to generate infection-competent, albeit morphologically and functionally incomplete, secondary spores, without increasing AMF biomass (Sugiura et al ., 2020). Unlike those signaling molecules, myristate enhanced both intraradical and extraradical fungal biomasses in our study, likely due to its dual role as a signaling molecule and a C source for AMF.…”
Section: Discussionmentioning
confidence: 99%